Two new tanaidaceans (Crustacea: Peracarida) from Portuguese submarine canyons (NE Atlantic, West Iberian Margin) - García-Herrero, Álvaro; Esquete, Patricia; Cunha, Marina R. (European Journal of Taxonomy, 2021)
The Tanaidacea are ubiquitous and amongst the most abundant taxa in the deep sea. However, their diversity in submarine canyons remains largely unknown. Here, two new species and a new genus of Paratanaoidea are described. Paranarthrura cousteaui sp. nov. is distinguished by the combination of the following characters: post-cheliped sclerites not fused, presence of one seta in the maxilliped endite, one long midventral seta in cheliped, one penicillate seta in the basis of pereopods 4–6, uropod endopod bi-articulated and uropod exopod shorter than endopod article 1. This species was found at the upper reaches of three Portuguese canyons, Cascais, Setúbal and Nazaré Canyons, and the adjacent open slope, between 897 and 1001 m water depths. Tirana vallis gen. et sp. nov. presents a combination of the characters that define the other two genera of Paranarthrurellidae, Paranarthrurella and Armatognathia, but also unique characters within the family: the antenna, cheliped and uropod are more elongate than the rest of the species; the pereopods 4–6 carpus spines reach at least half of the length of the propodus and the propodus of pereopods 4–6 have ramified subdistal spines. This species was found at the middle reaches of Setúbal Canyon (3214–3219 m water depth).